Penggunaan Media Audio Visual di Masa Pandemi Covid-19 Pada Pembelajaran IPS Siswa Kelas V di SD Inpres Tello Baru 1/1 - Irviana, Ira (DIKDAS MATAPPA: Jurnal Ilmu Pendidikan Dasar, 2021)
The purpose of this study is to describe how instructors and students used audio-visual media during the COVID-19 pandemic in terms of planning, implementation, evaluation, and aspects linked to the use of audio-visual media in science courses for class V at SD Inpres Tello Baru 1/ 1. This study employs qualitative research methods such as observation, interviews, and documentation to acquire data. The findings revealed that the teacher's usage of audio-visual media for planning included preparing the syllabus, lesson plans, creating learning materials in the form of learning videos, preparing audio-visual media instruments in the form of laptops or smartphones, and using the Whatsapp application. In terms of teacher implementation, the teacher inquires about students' well-being, requests that students pray before learning, attends to students, communicates learning objectives, sends material via Whatsapp, communicates material via video, and requests that students comprehend the material on the video. In terms of assessment, the teacher completes the learning materials, returns the evaluation task, and assigns homework.